ANALYSIS OF WILLINGNESS TO PAY FOR C4 PULEN RICE PRODUCED BY UD. RATIH - Ni Komang Ayu Dirgantari; Ni Luh Prima Kemala Dewi (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2025)
Consumers' Willingness to Pay for C4 pulen rice produced by UD. Ratih in Bali is analyzed in this study, aiming to identify consumer characteristics and market segmentation, calculate WTP values, and evaluate influencing factors. Employing a quantitative approach with the Contingent Valuation Method (CVM) and SEM-PLS, data were collected from 100 UD. Ratih consumers through questionnaires and interviews. The findings reveal that consumers are predominantly young (20-24 years), highly educated (59%), with middle income (IDR 3,000,000-IDR 5,000,000), and no family dependents (53%). The highest WTP was recorded for 10 kg packaging (IDR 2,417/kg), with consumer income as the most significant factor (p=0.000), followed by product price (p=0.000) and product quality (p=0.004). The quality of C4 rice—such as its softness and aroma—is a major attraction, although market competition and price fluctuations remain challenges. This study recommends marketing strategies that highlight local quality and utilize digital-based promotions to expand market reach.